Pengembangan Web Interaktif "Hai Si IPA" Untuk Meningkatkan Literasi Sains Di Sekolah Dasar - Dini Rosyada Mahmud; Arif Hidayat; Munzil Munzil; Muhibuddin Fadhli (Cetta: Jurnal Ilmu Pendidikan, 2023)
The key to students facing challenges in the 21st century is insight and skills in science literacy. In Indonesian elementary schools, it is noted that students' science literacy is still not maximally utilizing digital technology to learn science and science learning outcomes are still low. Based on the results of observations and interviews in elementary schools, it was found that blog teaching materials had never been used on ecosystem material, so the researcher's goal was to develop a blog teaching material "Hi Si IPA to improve the science literacy of grade V elementary school students. This research uses the ADDIE model (Analysis- Design- Development -Implement -Evaluate). Quantitative data analysis in the form of numbers from the results of expert validation of teaching materials, questionnaires of attractiveness, practicality, effectiveness, namely pretests and posttests. While qualitative data analysis is in the form of criticism and suggestions by teaching material experts, teachers, and students.  The results of teaching material expert validation are 81% with very valid criteria. The trial of the "Hi Si IPA" blog in a small group of 5 students with a questionnaire of students' initial knowledge and a pretest questionnaire the results were low, while the results of the student interest questionnaire were 89% with very interesting criteria. The field trial was 25 students in class V, the results of the student and teacher practicality questionnaire were 88.5%. Analysis of the increase in science literacy using the normality gain test from the pretest and posttest results of students was found to increase 84% with high criteria. So that the blog "Hi Si IPA" is feasible to use, attracts students' interest, is practical for learning, and can improve science literacy.